Advanced clinical stage Parkinson’s disease is linked to proinflammatory and regulatory blood cell populations - Ichikawa-Escamilla, Eduardo; Espinosa-Cárdenas, Raquel; Leyva-Hernández, Jaquelin; Álvarez-Luquín, Diana D.; Arce-Sillas, Asiel; Adalid-Peralta, Laura (Neurological sciences, 2025)
The clinical stage of Parkinson's disease (PD) can be assessed using the Hoehn & Yahr (H&Y) and MDS-UPDRS scales. Both neuroinflammation and peripheral inflammation have been linked to advanced PD. This study aimed to investigate changes in the peripheral regulatory and proinflammatory immune response in PD patients and its relationship to advanced disease. Forty-six patients were classified by clinical stage according to H&Y as "mild," "moderate," and "severe." Twenty-two healthy subjects were included as controls. MDS-UPDRS, Beck, and Schwab & England scores were measured in patients and controls. Proinflammatory and regulatory cell populations were quantified by flow cytometry in each group. As expected, total MDS-UPDRS scores and MDS-UPDRS section scores increased significantly with disease severity. Interestingly, decreased counts of activated Tregs, functional Bregs, and IL-10-producing functional Bregs were found in PD patients compared to controls. Such decrease progresses in parallel with the disease in patients. In addition, the level of activated Tregs correlated positively with Schwab & England score. The levels of pro-inflammatory cells (Th2 IL-13 + , Th2 IL-4 + , and Th17 IL6 +) were decreased in patients compared to controls. However, the levels of IL-6 producing Th17 cells showed a significant positive correlation with MDS-UPDRS III score. These results suggest a relationship between the patient's peripheral immune response and developing advanced disease. Patients with higher levels of regulatory cells have a less progressive disease and a better quality of life than those with a peripheral pro-inflammatory profile. Thus, it is necessary to develop therapeutic strategies that contribute to the regulation of inflammation in PD.